2017
DOI: 10.1111/tbed.12605
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study to quantify the prevalence of avian influenza viruses in poultry at intervention and non-intervention live bird markets in central Vietnam, 2014

Abstract: In Vietnam, live bird markets are found in most populated centres, providing the means by which fresh poultry can be purchased by consumers for immediate consumption. Live bird markets are aggregation points for large numbers of poultry, and therefore, it is common for a range of avian influenza viruses to be mixed within live bird markets as a result of different poultry types and species being brought together from different geographical locations. We conducted a cross-sectional study in seven live bird mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
1
12
2
Order By: Relevance
“…LBMs in this study (14%) was higher than the AIV positivity prevalence of 6.9% among LBMs in the centre of Vietnam identified by Chu et al (2017), and 5.8% in the north of Vietnam identified by Thuy et al (2016). Assuming these differences in prevalence are real and not due to, for example, seasonal and yearly fluctuations in the incidence of AI, our results imply that LBMs in southern Vietnam play a more dominant role in maintaining AIV circulation in the poultry population compared to other areas of the country.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…LBMs in this study (14%) was higher than the AIV positivity prevalence of 6.9% among LBMs in the centre of Vietnam identified by Chu et al (2017), and 5.8% in the north of Vietnam identified by Thuy et al (2016). Assuming these differences in prevalence are real and not due to, for example, seasonal and yearly fluctuations in the incidence of AI, our results imply that LBMs in southern Vietnam play a more dominant role in maintaining AIV circulation in the poultry population compared to other areas of the country.…”
Section: Discussioncontrasting
confidence: 65%
“…Although LBM closures break the viral amplification cycle, AIVs are often re-introduced once they are re-opened (Kung et al, 2003). A previous Vietnamese study investigating the effectiveness of virus control measures in LBMs showed no differences in AIV prevalence between LBMs with and without biosecurity interventions (Chu et al, 2017). One interpretation of these findings is that the introduction of AIV into LBMs occurs continuously.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…S1). Moreover, all H5 HPAIVs in our surveillance were isolated in LBMs and LBM-like locations, indicating that LBMs play important roles for virus persistence and dissemination 18,28 . These findings confirmed relatively constant epidemiology of H5 HPAIVs in regards that abundance of waterfowl species and live poultry trading activities facilitate H5 HPAIV persistence and these elements should be primary targets of the surveillance and control system.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, LBMs are home to many poultry species and contain pathogens from various places. LBMs provide a very favorable environment for the avian influenza virus to exchange and disperse [6,7]. Previous studies have shown that the poultry markets in Vietnam have many different subtypes of influenza viruses such as H3, H4, H5, H6, H7, and H9 and N1, N2, N3, N6, and N8 [8, 9].…”
Section: Introductionmentioning
confidence: 99%